New insights into the optimal management of COPD: extracts from CHEST 2021 annual meeting (October 17–20, 2021). Issue 4 (3rd April 2022) - Quint, Jennifer; Montonen, Jukka; Singh, Dave; Wachtel, Herbert; Attick, Sharon; Palli, Swetha; Frazer, Monica; Willey, Vincent; Giessel, Glenn
ABSTRACT: Introduction: Discordance between real-world prescribing patterns and global treatment guidelines for the treatment of chronic obstructive pulmonary disease (COPD) with inhaled single or dual long-acting bronchodilator maintenance therapy is increasingly being reported in the literature, particularly with regard to addition of inhaled corticosteroids (ICS). Patient-related factors, e.g. inhalation technique and inspiratory flow, are key to disease control in COPD. Treatment discordance and patient-related factors can lead to high-cost side effects and sub-optimal treatment benefit; furthermore, the COVID-19 pandemic has led to new challenges in COPD management. Areas Covered: This article summarizes a series of presentations sponsored by Boehringer Ingelheim and delivered at the annual CHEST congress 2021 (October 17–20, 2021) that explored new insights into the optimal management of COPD. Expert Opinion/Commentary: There is a concerning high degree of discordance with GOLD recommendations. Dual therapy without addition of ICS does not increase exacerbation risk and could reduce pneumonia risk, and unnecessary prescription of triple therapy has financial implications. Clinic-based spirometry may not reflect the home setting, and training is required; inhalers that operate independently of users' inhalation profiles should be considered. Integration of digital healthcare solutions into clinical studies is suggested in the post-COVID setting, although further evaluation is required.